Negotiating family planning messages among Malawian men: A case study of vasectomy messages aimed at men in the Dedza and Karonga districts of Malawi - Ntaba, Jolly Maxwell (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
Since the 1990s, vasectomy, the principal non-barrier method of contraception offered to men, has been vigorously promoted in Malawi, as a safe, effective and inexpensive form of birth control. Despite this marketing, the method has been chosen by only an estimated 0.01% of men in Malawi. This compares to about 11% of contraceptive using Malawian women, who have opted for tubal ligation, a more expensive and hazardous surgical procedure. Previous studies into this low uptake of vasectomy among men in Malawi, and other studies that have explored why no African country currently has a vasectomy rate of more than 1% of men, implicate cultural beliefs and traditional social practices among the key barriers to the diffusion of this particular innovation i.e. this method of contraception. Campaigns share new information in the hope that they will shift their audiences' knowledge, and lead to changes in attitudes and practices, including the uptake of vasectomy. Social Marketing campaigns, even when they set out to explicitly accommodate these beliefs and challenge particular practices in order to promote various methods of contraception, are often inadequately conceived and sometimes poorly executed. Drawing on well-established theoretical perspectives developed by Cultural Studies scholars, including Reception Analysis and Thematic Analysis, this study investigates how men in two purposively selected districts of Karonga and Dedza in Malawi, interpret Social Marketing messages encouraging them to undergo vasectomies. The study examines key media texts and the nature of the involvement of a group of peer educators, dubbed 'male champions' in a 2017-2018 campaign by one of the leading Malawian providers of family planning services, the NGO Banja La Mtsogolo (BLM), to promote vasectomy. This is a purely qualitative case study that seeks to understand why these often-well-resourced campaigns have so little impact on the behaviour change they hope to inspire. Through individual interviews with the campaign's designers, implementers, peer educators, focus group discussions with the campaign's audiences, a close reading of texts used in the campaign, and observation, this study explores the circuits of communication and culture, through mechanisms of resonance, disconnection and even cognitive dissonance between the 'encoders' of the family planning messages and the decoders i.e. the intended audiences of the campaign. The study argues that as a result of several 'modernist' assumptions and outlooks, the campaign was unable to fully grasp the complex and contextually nuanced socio-cultural practices that factor into consideration of the campaign's messages and the non-adoption of the proposed vasectomy method. The study further reveals, as many other studies have also observed, that the interpretation of the text promoting vasectomy is a complex process that is significantly shaped by the worldviews and lived experiences of the audiences. These views, as this study explores, are often complex and contradictory, interfacing aspirations of modernity with deeply held 'traditional' beliefs and practices. Although the campaigns are effective at transferring knowledge "“ it finds most targeted men have a relatively good understanding of the method and its efficacy "“ their prevailing socio-cultural attitudes and dispositions provide a strong countervailing discourse to the preferred reading of the campaign messages. This discourse exhorts having children, or the capacity to have children, even after a man has had several before, in current or previous marriages, or even in old age, as desirable and 'rational'. The study therefore proposes, arising out of this detailed ethnographic research, a revised approach that argues that several social and cultural 'vectors' or 'spheres of influence' need to be considered in new ways, in order to develop meaningful interventions in the promotion of vasectomy. This includes specific strategies to understand and challenge: 1. The enduring power of social stigma and scorn, and the notion of social shame. 2. The deep interplay between fertility and having children to notions of marriage, even in second or third marriages, and the interplay with perceptions of economic 'value' of children in the domestic political economy of marriage. 3. The embedded nature of provable fertility to notions of manhood. 4. The complex and nuanced involvement, at many levels, of broader social/family structures/personages in 'personal' decisions. 5. Forms of 'hyperbolic discounting', i.e. the calculating of precarious futures in various scenarios and its impact on current shorter-term calculations and gratifications. 6. Unusually high rates of infidelity in marriage, and seemingly low levels of trust in many partnerships. 7. The key role of interpersonal communication, i.e. the face-to-face elements of what are usually media-centric Social Marketing campaigns. The study recommends a more layered and nuanced approach to the promotion of vasectomy, propelled by a deeper understanding of these kinds of contexts and the interpretive power of the intended audience, as well as more nuanced segmentation of audiences, and more judicious use of peer-educators to support and deepen the mass media components of these communication campaigns.
Keywords: Social marketing -- Malawi; Vasectomy -- Social aspects -- Malawi; Malawians -- Attitudes; Men -- Malawi -- Attitudes; Men -- Conduct of life -- Malawi; Men -- Sexual behavior -- Malawi; Masculinity -- Malawi; Reproductive health in mass media -- Malawi; Reproductive health services -- Malawi